2004
DOI: 10.1080/02791072.2004.10399728
|View full text |Cite
|
Sign up to set email alerts
|

MDMA/Ecstasy Use Among Young People in Ohio: Perceived Risk and Barriers to Intervention

Abstract: In the past several years, the use of MDMA (Ecstasy) has increased substantially in the United States and in many countries around the world. Although this increase has been associated with the dance club and rave scenes, Ecstasy use has expanded into new settings. At the same time, the diversity of people using the drug has also grown. Given the increasing, although unclear, evidence that MDMA has the potential to cause neurotoxicity and various psychological problems under certain conditions among humans, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 27 publications
0
27
0
2
Order By: Relevance
“…Because most ecstasy users are or will become polydrug users in young adulthood (Carlson et al, 2004;Martins et al, 2005;Martins et al, 2007), our findings can be useful to prevention programs that target adolescent polydrug use and not only ecstasy use. Prevention programs may need to consider different strategies in changing attitudes towards drug use once marijuana use has begun.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Because most ecstasy users are or will become polydrug users in young adulthood (Carlson et al, 2004;Martins et al, 2005;Martins et al, 2007), our findings can be useful to prevention programs that target adolescent polydrug use and not only ecstasy use. Prevention programs may need to consider different strategies in changing attitudes towards drug use once marijuana use has begun.…”
Section: Discussionmentioning
confidence: 92%
“…For example, one school drug-prevention program based on three theoretical models (health belief model- Rosenstock et al, 1988, social learning model-Bandura, 1985, and the self-efficacy theory-Bandura, 1977) was able to decrease positive attitudes towards marijuana use and decrease marijuana use among girls who had initiated tobacco or marijuana use (Longshore et al, 2007). Researchers have suggested that prevention programs that target a decrease in ecstasy use should focus on the more common acute and sub-acute side-effects of ecstasy use in order to decrease approval of ecstasy use (Baggott, 2002;Carlson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study results have shown that peers influence the nature of Ecstasy use within social networks (Beck & Rosenbaum, 1994;Carlson et al, 2004;Gourley, 2004;Hansen et al, 2001;Schensul et al, 2005). Research findings also reveal that friends are one of the most common and important sources of information about Ecstasy's effects Gamma et al, 2005;Murphy et al, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…The evolving, possibly more negative, representations of a specific drug offer large incentives for the willingness to experiment with it. Therefore, one of the most important influences on drug use may be "folk" perceptions of the acceptability of the drug (Carlson, Falck, McCaughan, & Siegal, 2004).…”
Section: Shifting Drug Trendsmentioning
confidence: 99%